2017
DOI: 10.3389/fnhum.2017.00440
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of External Forces on Wrist Proprioception

Abstract: Proprioception combines information from cutaneous, joint, tendon, and muscle receptors for maintaining a reliable internal body image. However, it is still a matter of debate, in both neurophysiology and psychology, to what extent such body image is modified or distorted by a changing haptic environment. In particular, what is worth investigating is the contribution of external forces on our perception of body and joint configuration. The proprioceptive acuity of fifteen young participants was tested with a J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Another main finding of this study is the anisotropy of wrist position sense, in both the perception of movement direction and extent. Particularly, our results should be compared with what has been found in previous works which investigated proprioception limited to FE and RUD directions in terms of extent of movement ( Cappello et al, 2015 ; Marini et al, 2016a , b , 2017a ). Our results suggest that error in the perception of movement extent is higher along the RUD than the FE plane.…”
Section: Discussionmentioning
confidence: 78%
“…Another main finding of this study is the anisotropy of wrist position sense, in both the perception of movement direction and extent. Particularly, our results should be compared with what has been found in previous works which investigated proprioception limited to FE and RUD directions in terms of extent of movement ( Cappello et al, 2015 ; Marini et al, 2016a , b , 2017a ). Our results suggest that error in the perception of movement extent is higher along the RUD than the FE plane.…”
Section: Discussionmentioning
confidence: 78%
“…Besides, Mugnosso et al revealed that muscle fatigue, which inputted abundance of proprioception, could decrease proprioceptive bias but not proprioceptive precision ( Mugnosso et al, 2019 ). However, external forces that might not be able to input enough proprioception as the repeated active movements of what fatigue protocol achieved failed to affect proprioceptive bias ( Kuling et al, 2013 ; Marini et al, 2017a ). Combined with this study, proprioception input from distal upper extremity induced directly by rPMS and indirectly by extension movements of the wrist joint could only improve proprioceptive bias but did not influence the experience of joint position matching; therefore, proprioceptive precision remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly adopted PS tests, namely ITM [54], [55], [74], [77]- [82] and CTM [1], [48], [60], [70], [73], [83]- [86] tests, were considered for testing PS in this study. ITM tests and CTM tests with different levels of external torque could be performed with the developed device as follows.…”
Section: A Simple Elbow Device For Assessing Position Sense Under Dif...mentioning
confidence: 99%
“…For instance, one can grasp a cup of coffee and bring it to her/his mouth to drink regardless of how much coffee is in it; one can move her/his arm to the desired position without looking at it under the downward gravitational force; and one can lift a book that s/he wants to read to the vicinity of her/his face. For these tasks, in the processing of the PS, external force/torque information, obtained from peripheral proprioceptors (e.g., Golgi tendon organ), may be used [1], [45]- [49], [54]- [60] in addition to the position information from the proprioceptors in muscle, skin, and joint. Furthermore, the PS is determined not only by the afferent feedback from the muscle, joint, and cutaneous proprioceptors but also by the efferent motor commands to the muscle (effort-based signal) [1], [2], [49], which are closely related to the sense of effort [1], [61]- [63] and provide an estimate of the intended posture [2], [56], [64], [65].…”
mentioning
confidence: 99%
See 1 more Smart Citation